Intra-observer reproducibility and inter-observer agreement of Fels skeletal age assessments among male tennis players 8-16 years - Paulo Sousa-; Manuel J. Coelho-; Jorge M. Celis-Moreno; Daniela C. Costa; Diogo V. Martinho; Luís P. Ribeiro; Tomas Oliveira; João Gonçalves-Santos; Oscar M. Tavares; Joaquim M. Castanheira; Telmo Pereira; Jorge Conde; et al. (BMC, 2023)
Abstract Background Skeletal age (SA) is an estimate of biological maturity status that is commonly used in sport-related medical examinations. This study considered intra-observer reproducibility and inter-observer agreement of SA assessments among male tennis players. Methods SA was assessed with the Fels method in 97 male tennis players with chronological ages (CA) spanning 8.7-16.8 years. Radiographs were evaluated by two independent trained observers. Based on the difference between SA and CA, players were classified as late, average or early maturing; if a player was skeletally mature, he was noted as such as an SA is not assigned. Results The magnitude of intra-individual differences between repeated SA assessments were d = 0.008 year (observer A) and d = 0.001 year (observer B); the respective coefficients of variation were 1.11% and 1.75%. Inter-observer mean differences were negligible (t = 1.252, p = 0.210) and the intra-class correlation coefficient was nearly perfect (ICC = 0.995). Concordance of classifications of players by maturity status between observers was 90%. Conclusion Fels SA assessments were highly reproducible and showed an acceptable level of inter-observer agreement between trained examiners. Classifications of players by skeletal maturity status based on assessments of the two observers were highly concordant, though not 100%. The results highlight the importance of experienced observers in skeletal maturity assessments.